Silver solder paste for large-area packaging interconnection and preparation method and application thereof

By introducing silver oxide particles and silver particles into the silver solder paste, the problem of insufficient shear strength of the existing silver solder paste connection layer is solved, and the high reliability effect of large-area packaging interconnection of wide-bandgap semiconductor devices is achieved.

CN118342158BActive Publication Date: 2025-04-11SOLDERWELL MICROELECTRONIC PACKAGING MATERIALS CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410291331.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-14
Publication Date
2025-04-11
Estimated Expiration
2044-03-14

AI Technical Summary

Technical Problem

The shear strength of the connecting layer formed by the existing silver solder paste after sintering is low, which cannot meet the needs of large-area packaging interconnection of wide-bandgap semiconductor devices.

Method used

By introducing silver oxide particles and silver particles, the mass ratio of silver particles to silver oxide particles is controlled to be (5-35): 1, and the mass percentage in the silver solder paste is controlled to be 80-98%, so as to improve the density and shear strength of the connection layer after sintering.

Benefits of technology

Sintering is achieved at a low temperature not higher than 300°C and a low pressure of 0 to 1 MPa to form a connecting layer with high shear strength and good density, and is suitable for large-area packaging interconnection of wide-bandgap semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118342158B_ABST
    Figure CN118342158B_ABST
Patent Text Reader

Abstract

The present invention discloses a silver solder paste for large-area packaging interconnection, and a preparation method and application thereof. The silver solder paste comprises silver particles, silver oxide particles and a solvent, wherein the mass ratio of the silver particles to the silver oxide particles is (5-35):1, and the mass percentage of the silver particles to the silver oxide particles in the silver solder paste is 80-98%. The present invention introduces a compound of silver oxide particles and silver particles into the silver solder paste, so that the silver solder paste can be sintered at a low temperature not higher than 300°C and a low pressure of 0-1MPa, thereby realizing large-area (≥40×40mm) wide-bandgap semiconductor devices. 2 ) packaging interconnection, the connection layer formed by sintering is uniform and dense, with high shear strength, good bonding between the connection layer and the device substrate, and high reliability of large-area packaging interconnection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor device packaging, and in particular to a silver solder paste for large-area packaging interconnection and a preparation method and application thereof. Background Art

[0002] Broadband semiconductors generally refer to semiconductor materials with a band gap greater than 2.0 eV at room temperature. Compared with ordinary semiconductors, wide-bandgap semiconductor devices can work normally at temperatures above 250°C, and also have very high breakdown voltage and operating frequency, and have very good application prospects in electric vehicles.

[0003] The prior art usually uses tin-lead solder or silver solder paste to coat the connection surface of the electronic device substrate and stack them together to form a "sandwich" structure in which the substrate, coating, and substrate are stacked in sequence. After the sintering process, the coating is sintered to form a connection layer. However, the melting point of tin-lead solder is relatively low, and it cannot meet the requirements of normal operation of wide-bandgap semiconductor devices at temperatures above 250°C. The melting point of silver in silver solder paste is above 900°C, which can meet the high-temperature operation requirements of wide-bandgap semiconductor devices. However, the connection layer formed by the silver solder paste after sintering has the defect of low shear strength, so that the existing silver solder paste cannot be well applied to the large-area packaging interconnection structure of wide-bandgap semiconductor devices. For example, the invention patent with publication number CN111843287A discloses a nano silver solder paste, which includes flaky nano silver and an organic solvent carrier mixed with each other, which forms a connection layer after sintering, and the shear strength of the connection layer is less than 36MPa.

[0004] Therefore, there is an urgent need to develop a silver solder paste with high shear strength for large-area packaging interconnection to meet the needs of wide-bandgap semiconductor devices to work normally at temperatures above 250°C. Summary of the invention

[0005] Based on the defects of the prior art, the purpose of the present invention is to provide a silver solder paste for large-area packaging interconnection and its preparation method and application. The present invention introduces silver oxide particles and silver particles to compound, so that the silver solder paste is suitable for large-area (≥40×40mm) wide-bandgap semiconductor devices. 2 ) packaging interconnection, high shear strength, and high reliability of large-area packaging interconnection.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a silver solder paste for large-area packaging interconnection, comprising silver particles, silver oxide particles and a solvent, wherein the mass ratio of the silver particles to the silver oxide particles is (5-35):1, and the mass percentage of the silver particles to the silver oxide particles in the silver solder paste is 80-98%.

[0008] The inventors have found through research that by controlling the mass ratio of silver particles to silver oxide particles at (5-35):1, and controlling the mass percentage of the silver particles to the silver oxide particles in the silver solder paste at 80-98%, the doping ratio of silver oxide in the silver solder paste is moderate. During the sintering process, the silver oxide particles can self-decompose to produce silver element, which has a high driving force and can reduce the porosity of the silver solder paste after sintering, thereby improving the density of the connection layer formed by the sintering of the silver solder paste. The decomposition of silver oxide can release oxygen, which is beneficial to promote solvent decomposition and gas discharge during the sintering process, avoid sintering residues, and enable the silver solder paste to be sintered at a low temperature not higher than 300°C and a low pressure of 0-1MPa, realizing large-area (≥40×40mm) wide-bandgap semiconductor devices. 2 ) packaging interconnection, the shear strength of the connection layer formed by sintering is high, and the reliability of large-area packaging interconnection is high.

[0009] As a preferred embodiment of the present invention, the particle size of the silver particles is 300 to 1500 nm.

[0010] As a preferred embodiment of the present invention, the particle size of the silver oxide particles is 1 to 5 μm.

[0011] As a preferred embodiment of the present invention, the mass ratio of the silver particles to the silver oxide particles is (15-30):1.

[0012] Furthermore, the mass ratio of the silver particles to the silver oxide particles is (15-25): 1, and the mass percentage of the silver particles to the silver oxide particles in the silver solder paste is 85-90%. When the above conditions are met, the connection layer formed by sintering the silver solder paste has better compactness and higher shear strength.

[0013] As a preferred embodiment of the present invention, the solvent is an alcohol-based solvent, and the number of carbon atoms in the molecular formula of the alcohol-based solvent is not greater than 10.

[0014] In a second aspect, the present invention provides a method for preparing a silver solder paste for large-area packaging interconnection as described in the first aspect, comprising the following steps:

[0015] S1, mixing the silver oxide particles and the solvent uniformly to obtain a mixed turbid liquid;

[0016] S2, mixing the silver particles and the mixed turbid liquid obtained in step S1 evenly to obtain the silver solder paste.

[0017] In a third aspect, the present invention provides a use of the silver solder paste for large-area packaging interconnection as described in any one of the first aspects in preparing a semiconductor device packaging interconnection structure.

[0018] As a preferred embodiment of the present invention, the semiconductor device package interconnection structure comprises a first substrate, a connection layer and a second substrate which are sequentially stacked and connected, and the connection layer is formed by sintering the silver solder paste through a sintering process.

[0019] Furthermore, the heating rate of the sintering process is 3-10°C / min, the sintering temperature is 250-400°C, the sintering time is 20-60min, the sintering pressure is 0-1MPa, and the sintering atmosphere is air.

[0020] In the present invention, the sintering pressure refers to the auxiliary pressure applied to the semiconductor device package interconnection structure, rather than the gas pressure of the sintering atmosphere. A sintering pressure of 0 means that no auxiliary pressure is applied.

[0021] Furthermore, the first substrate and the second substrate are the same or different sheet structures, and the sheet structure is any one of a metal sheet, a ceramic sheet with metal attached to the surface, and a silicon sheet with metal attached to the surface.

[0022] Furthermore, the metal in the sheet structure includes at least one of gold, silver and copper.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The invention introduces silver oxide particles and silver particles into the silver solder paste, so that the silver solder paste can be sintered at a low temperature not higher than 300°C and a low pressure of 0-1MPa, so as to realize the large-area (≥40×40mm) wide-bandgap semiconductor device. 2 ) packaging interconnection, the connection layer formed by sintering is uniform and dense, with high shear strength, good bonding between the connection layer and the device substrate, and high reliability of large-area packaging interconnection. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscope image of the middle area of ​​the cross section of the package interconnect structure of Example 1 of the present invention;

[0026] Figure 2 This is a scanning electron microscope cross-section of the edge region of the package interconnect structure of Example 1 of the present invention. DETAILED DESCRIPTION

[0027] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used ordinary instruments.

[0028] The following shear strength test method is: cut the package interconnect structure into pieces with an area of ​​4.5×4.5mm 2 A small piece is selected as the sample to be tested. The connection area between the connection layer and each substrate in the sample to be tested is 4.5×4.5mm 2 The sample to be tested is fixed on the fixing fixture of the shear force tester, with the first substrate facing upwards. The first substrate is pushed by the pusher to compress the sample to be tested. The pushing force (i.e., shear force) applied when the connecting layer breaks is recorded. The shear force is divided by the connecting area (4.5×4.5mm 2 ), and obtain the shear strength of the connecting layer.

[0029] The following porosity test method is as follows: the package interconnect structure is embedded and cured with epoxy resin and then cured at room temperature for 12 hours; a metallographic cutting machine is then used to cut the sample with a cutting blade perpendicular to the sample surface to expose the connection section; the obtained cross-sectional sample is coarsely ground, finely ground, and polished to prepare the cross-sectional sample of the connection layer; a scanning electron microscope is used to photograph the cross section of the package interconnect structure, and matlab is used to grayscale the image, wherein the pores in the connection layer area are black, and the porosity is obtained by calculating the area ratio of the black pores in the photographed connection layer area.

[0030] Unless otherwise specified, the components and raw materials used in the embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0031] Examples 1 to 17 and Comparative Examples 1 to 4

[0032] The embodiments and comparative examples of the silver solder paste of the present invention, the silver solder paste is composed of silver particles, silver oxide particles and a solvent, the mass ratio of the silver particles to the silver oxide particles is shown in Table 1, the mass percentages of the silver particles and the silver oxide particles in the silver solder paste are shown in Table 1, the solvent is propylene glycol, and the average particle size of the silver particles and the average particle size of the silver oxide particles are shown in Table 1.

[0033] The preparation method of the silver solder paste comprises the following steps:

[0034] S1, mixing the silver oxide particles and the solvent uniformly to obtain a mixed turbid liquid;

[0035] S2, mixing the silver particles and the mixed turbid liquid obtained in step S1 evenly to obtain the silver solder paste.

[0036] The application of the silver solder paste described in this embodiment in preparing a semiconductor device packaging interconnection structure comprises the following steps:

[0037] (1) Select an area of ​​40×40mm 2 and a copper sheet with a thickness of 1 mm, and an area of ​​60×60 mm2 The copper sheet with a thickness of 1 mm was polished with 3000# sandpaper to remove the copper oxide on the surface; the polished copper sheet was then ultrasonically washed in anhydrous ethanol for 2 minutes to remove surface impurities, and then the washed copper sheet was placed in a vacuum drying oven and dried at 60°C for 3 minutes to remove the ethanol;

[0038] (2) The surface of the copper sheet treated in step (1) was electroplated with a silver layer of 5 μm, and then the electroplated copper sheet was ultrasonically cleaned in anhydrous ethanol for 2 minutes, and then the washed copper sheet was placed in a vacuum drying oven and dried at 60° C. for 3 minutes to remove the ethanol, and the area was 40×40 mm. 2 The copper sheet plated with silver is the first substrate, with an area of ​​60×60mm 2 The copper sheet plated with a silver layer is the second substrate;

[0039] (3) Apply silver solder paste to the connecting surface of the second substrate (the area of ​​the connecting surface is 60×60 mm) by screen printing. 2 ), a coating is formed on the substrate, the thickness of the coating is 80 μm, a first substrate is placed on the coating, and the contact area between the first substrate and the coating is 40×40 mm 2 , forming a stacking structure;

[0040] (4) placing the stacked structure obtained in step (3) in a pressure-assisted sintering furnace for sintering, and then cooling naturally to obtain a package interconnection structure.

[0041] During sintering in Example 1, the temperature was raised to 300° C. at a heating rate of 5° C. / min, and pressureless sintering was performed at 300° C. for 30 min. The sintering process parameters of other examples and comparative examples are shown in Table 1.

[0042] Table 1

[0043]

[0044]

[0045] The shear strength test and porosity test were performed on the connection layer of the package interconnection structure obtained in each embodiment and comparative example. The test results are shown in Table 2 below.

[0046] Table 2

[0047] Test items Shear strength(MPa) Porosity (%) Example 1 38.7 20.3 Example 2 22.7 28.1 Example 3 31.2 24.2 Example 4 19.8 29.7 Example 5 31.6 23.3 Example 6 29.7 24.9 Comparative Example 1 13.1 31.9 Example 7 27.2 26.2 Comparative Example 3 12.1 29.1 Comparative Example 4 11.4 36.9 Example 8 32.9 23.6 Example 9 27.3 26.1 Example 10 30.7 20.3 Comparative Example 4 17.4 30.5 Embodiment 11 23.1 19.3 Example 12 36.8 20.8 Embodiment 13 32.5 21.1 Embodiment 14 27.3 22.6 Embodiment 15 25.6 22.9 Example 16 31.4 21.8 Embodiment 17 38.1 21.1

[0048] As can be seen from Examples 1 to 17, the present invention introduces silver oxide particles into the silver solder paste, and controls the mass ratio of silver particles to silver oxide particles to be (5 to 35):1, and controls the mass percentage of silver particles to silver oxide particles in the silver solder paste to be 80 to 98%, so that the silver solder paste is suitable for sintering at a low temperature not higher than 300°C and a low pressure of 0 to 1 MPa to form a connection layer with good density and high shear strength. The porosity of the connection layer is not greater than 29.7%, and the shear strength is not less than 19.8 MPa, which is suitable for large-area packaging interconnection of wide-bandgap semiconductor devices. When the mass ratio of the silver particles to the silver oxide particles is (15 to 25):1, and the mass percentage of the silver particles to the silver oxide particles in the silver solder paste is 85 to 90%, the connection layer formed by sintering the silver solder paste has better density, a porosity of not greater than 24.2%, and a higher shear strength, with a shear strength of not less than 30.7 MPa. For example, the connection layer prepared in Example 1 has good density and small pores, and its morphology is as follows: Figures 1-2 shown.

[0049] Compared with Examples 1 to 7, the proportion of silver oxide particles in the silver solder paste in Comparative Examples 1 and 3 is relatively excessive, and the density and shear strength of the connecting layer are significantly deteriorated. This indicates that excessive silver oxide decomposes to produce excessive oxygen, and part of the oxygen participates in the decomposition of organic matter and is consumed, but the excess oxygen does not participate in the reaction and still needs to be discharged, which in turn reduces the density of the connecting layer.

[0050] Compared with Examples 1 to 7, the proportion of silver oxide particles in the silver solder paste in Comparative Example 2 is relatively too small, and the density and shear strength of the connecting layer are significantly deteriorated. This indicates that the oxygen produced by the decomposition of a small amount of silver oxide is not sufficient to fully decompose the organic matter, so that there are still organic matter remaining in the connecting layer after sintering.

[0051] Compared with Example 1 and Examples 8 to 11, the mass percentages of silver particles and silver oxide particles in the silver solder paste of Comparative Example 4 are too small, and the density and shear strength of the connecting layer are both reduced, which indicates that the relative content of organic matter in the silver solder paste is too much, and the amount of residual organic matter increases during the sintering process. However, the oxygen produced by the decomposition of silver oxide is limited, and it is impossible to ensure that the organic matter is fully decomposed, resulting in organic matter remaining after sintering, which will lead to a decrease in sintering density and shear strength.

[0052] Compared with Example 1 and Examples 8 to 10, the mass percentage of silver particles and silver oxide particles in the silver solder paste of Example 11 is too large, the density of the connecting layer is improved, but the shear strength of the connecting layer is reduced. This is mainly because organic matter can improve the wettability of the connecting interface. The relatively small content of organic matter in the silver solder paste will lead to reduced interface wetting effect, resulting in weakened interface connection after sintering, and then resulting in a decrease in the shear strength of the connecting layer.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A silver solder paste for large-area packaging interconnection, characterized in that: The invention comprises silver particles, silver oxide particles and a solvent, wherein the mass ratio of the silver particles to the silver oxide particles is (15-25):1, the mass percentage of the silver particles to the silver oxide particles in the silver solder paste is 85-90%, and the area of ​​the package interconnection is ≥40×40 mm 2 .

2. The silver solder paste for large area packaging interconnection as claimed in claim 1, characterized in that: The particle size of the silver particles is 300-1500 nm.

3. The silver solder paste for large area packaging interconnection as claimed in claim 1, characterized in that: The particle size of the silver oxide particles is 1 to 5 μm.

4. The silver solder paste for large area packaging interconnection as claimed in claim 1, characterized in that: The solvent is an alcohol-based solvent, and the number of carbon atoms in the molecular formula of the alcohol-based solvent is not greater than 10.

5. A method for preparing a silver solder paste for large-area packaging interconnection as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1, mixing the silver oxide particles and the solvent uniformly to obtain a mixed turbid liquid; S2, mixing the silver particles and the mixed turbid liquid obtained in step S1 evenly to obtain the silver solder paste.

6. Use of the silver solder paste for large-area packaging interconnection as claimed in any one of claims 1 to 4 in preparing semiconductor device packaging interconnection structure.

7. The use according to claim 6, characterized in that The semiconductor device package interconnection structure comprises a first substrate, a connection layer and a second substrate which are sequentially stacked and connected, and the connection layer is formed by sintering the silver solder paste through a sintering process.

8. The use according to claim 7, characterized in that The sintering process has a sintering temperature of 250-400° C., a sintering time of 20-60 min, a sintering pressure of 0-1 MPa, and an air atmosphere.

9. The use according to claim 7, characterized in that The first substrate and the second substrate are the same or different sheet structures, and the sheet structure is any one of a metal sheet, a ceramic sheet with metal attached to the surface, and a silicon sheet with metal attached to the surface.

10. The use according to claim 9, characterized in that The metal in the sheet structure includes at least one of gold, silver and copper.

Citation Information

Patent Citations

  • Nano-silver soldering paste, and preparation method and application thereof

    CN111843287A

  • Control of the porosity of metal pastes for pressure-free low temperature sinter-process

    CN101662080A

  • Electrically conductive bonding material, method of bonding with the same, and semiconductor device bonded with the same

    CN101875158A

  • Process and paste for contacting metal surfaces

    CN102430875A

  • Conductive paste and its manufacturing method

    JP2005267900A